2023
DOI: 10.3390/cells12232732
|View full text |Cite
|
Sign up to set email alerts
|

In Doxorubicin-Adapted Hodgkin Lymphoma Cells, Acquiring Multidrug Resistance and Improved Immunosuppressive Abilities, Doxorubicin Activity Was Enhanced by Chloroquine and GW4869

Naike Casagrande,
Cinzia Borghese,
Michele Avanzo
et al.

Abstract: Classical Hodgkin lymphoma (cHL) is a highly curable disease (70–80%), even though long-term toxicities, drug resistance, and predicting clinical responses to therapy are major challenges in cHL treatment. To solve these problems, we characterized two cHL cell lines with acquired resistance to doxorubicin, KM-H2dx and HDLM-2dx (HRSdx), generated from KM-H2 and HDLM-2 cells, respectively. HRSdx cells developed cross-resistance to vinblastine, bendamustin, cisplatin, dacarbazine, gemcitabine, brentuximab vedotin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…Doxorubicin is one of the current treatment regimens in HL, and their findings indicate that autophagy functions as a cellular mechanism to rescue tumor cells from apoptosis [ 27 ]. Confirming previous findings, co-administration of autophagy inhibitors was shown to reverse doxorubicin resistance in doxorubicin-resistant HL cells [ 29 ]. An extensive study on multiple HL cell lines found that inhibiting autophagy causes an increase in cell death compared to non-malignant B-cells [ 30 ].…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Doxorubicin is one of the current treatment regimens in HL, and their findings indicate that autophagy functions as a cellular mechanism to rescue tumor cells from apoptosis [ 27 ]. Confirming previous findings, co-administration of autophagy inhibitors was shown to reverse doxorubicin resistance in doxorubicin-resistant HL cells [ 29 ]. An extensive study on multiple HL cell lines found that inhibiting autophagy causes an increase in cell death compared to non-malignant B-cells [ 30 ].…”
Section: Resultssupporting
confidence: 85%
“…The results from our review showed studies supporting both sides of the argument. Autophagy was shown to have protective effects on cancer cells [ 27 , 29 , 30 , 33 ] but was also essential for cell death [ 28 , 31 , 32 , 36 ]. The conflicting conclusion reflects autophagy's complex cellular function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation